424. 1) (sina + cosa)² + (sina - cosa)² = sin²a + 2sinacosa + cos²a + sin²a - 2sinacosa + cos²a = 1 + 2sinacosa + 1 - 2sinacosa = 2.
3) 1/(1 + tg²a) + 1/(1 + ctg²a)= 1/(1 + tg²a) +1/(1 + 1/tg²a) = 1/(1 + tg²a) + 1/((tg²a + 1)/tg²a) = 1/(1 + tg²a + tg²a/(tg²a + 1) = (1 + tg²a)/(1 + tg²a) = 1.
5) (2 - sin²a - cos²a)/(3sin²a + 3cos²a) = (1 - sin²a + 1 - cos²a)/3 = (sin²a + cos²a)/3 = 1/3.
425. 1) (1 + 2sinacosa)/(sina + cosa)² = 1
(1 + 2sinacosa)/(sin²a + 2sinacosa + cos²a) = 1
(1 + 2sinacosa)/(1 + 2sinacosa) = 1
1 = 1
3) (2 - sina)(2 + sina) + (2 - cosa)(2 + cosa) = 7
4 - sin²a + 4 - cos²a = 7
8 - (sin²a + cos²a) = 7
8 - 1 = 7
7 = 7
Всюду использовалось основное тригонометрическое тождество:
sin²a + cos²a = 1;
а также:
tga•ctga = 1
Пошаговое объяснение:
2)3 1/7* 2/11= 22/7*2/11=4/7
3)4/7:8/11=11/14
4) 2-11/14= 1 3/14
1) 2 1/6 +8/15 =13/6+8/15=65/30+16/30=81/30
2)1/2:81/30= 1*30/2*81=5/27
3) 5/27*1 4/5=5/27*9/5=5*9/27*5=1/3
4)4 5/12-1/3=4 1/12